Control of Spatially Homogeneous Distribution of Heteroatoms to Produce Red TiO2 Photocatalyst for Visible‐Light Photocatalytic Water Splitting. Issue 7 (2nd January 2019) - Hong, Xingxing; Tan, Jun; Zhu, Huaze; Feng, Ningdong; Yang, Yongqiang; Irvine, John T. S.; Wang, Lianzhou; Liu, Gang; Cheng, Hui‐Ming
Abstract: The strong band‐to‐band absorption of photocatalysts spanning the whole visible‐light region (400–700 nm) is critically important for solar‐driven photocatalysis. Although it has been actively and widely used as a photocatalyst for various reactions in the past four decades, TiO2 has a very poor ability to capture the whole spectrum of visible light. In this work, by controlling the spatially homogeneous distribution of boron and nitrogen heteroatoms in anatase TiO2 microspheres with a predominance of high‐energy 001 facets, a strong visible‐light absorption spectrum with a sharp edge beyond 680 nm has been achieved. The red TiO2 obtained with homogeneous doping of boron and nitrogen shows no increase in defects like Ti 3+ that are commonly observed in doped TiO2 . More importantly, it has the ability to induce photocatalytic water oxidation to produce oxygen under the irradiation of visible light beyond 550 nm and also the photocatalytic reduction of water to produce hydrogen under visible light. These results demonstrate the great promise of using red TiO2 for visible‐light photocatalytic water splitting and also reveal an attractive strategy for realizing the wide‐spectrum visible‐light absorption of wide‐band‐gap oxide photocatalysts. Abstract : Sharp doping ! By controlling the spatially homogeneous distribution of boron and nitrogen heteroatoms in faceted anatase TiO2 microspheres, an extraordinary strong band‐to‐band visible‐light absorption spectrum with a sharp absorption edge has been achieved (see figure). The resultant red anatase TiO2 can induce photocatalytic water oxidation and reduction under visible light.